La naturaleza de la capitalización de créditos en la Sociedad Anónima - Herrada Bazán, Víctor (2019)
This paper examines capital increase by credit compensation in stock corporations, regulatedby article 202 LGS, in terms of one of the most controversial issues that Spanishdoctrine has raised: its legal status. This issue brings significant legal consequences inour system. This paper has a brief introduction about the functionality and the structureof the operation, a preliminary issue about what we actually look for when we ask forthe legal status of a phenomenon, an analysis of the theories proposed to determinethis in credit compensation and, finally, an opinion about it.